Moral decision making in adolescents: The effects of peer attachment, interpersonal affect, and gender. Issue 2 (8th February 2022) - Koenig, Scott; Gao, Yu
Abstract: Introduction: Sacrificial moral dilemmas are a useful tool for understanding how individuals reconcile concerns for aggregate welfare with the emotional aversion to deliberately, personally harming others. Yet little is known about how adolescents respond to such dilemmas, even though adolescence is a crucial period for moral development. The present study sought to investigate how adolescents respond to such dilemmas, with a focus on gender differences, age differences, and the role of two individual differences factors: peer attachment and dampened interpersonal affect. Methods: For this cross‐sectional study, 103 adolescents (mean age = 14.5, SD = 0.81, range = 12–16; 54% girls; 41% Black, 24% White, 15% multiracial, 9% Hispanic/Latin, 3% Other, 2% Asian/Pacific Islander, 1% Native American, 5% no response) were recruited from the local community (Brooklyn, NY, USA). Adolescents responded to a series of sacrificial moral dilemmas. Then, participants and their caregivers completed questionnaires to assess adolescents' callous‐unemotional traits (e.g., lack of empathy) and the quality of their peer relationships. Results: On average, participants endorsed committing personal harm for the greater good in 53% of their responses. Girls endorsed personal utilitarian sacrifice more than boys. Peer attachment, but not dampened interpersonal affect, was associated with increased endorsement of personal utilitarian sacrifice. Age and responses to dilemmas were not associated. Conclusions: Our results suggest that peer relationships are an important part of adolescent moral decision‐making, for girls in particular. Our results also indicate that adolescents' utilitarian responses to conventional sacrificial moral dilemmas do not reflect a decreased aversion to interpersonal harm.